Effects of yeast’s weight and fermentation time to percent yield of bioethanol from peatland - Ahmad Roni, Kiagus; Hastarina, Merisha; Herawati, Netty (International Journal of Engineering and Technology, 2019)
Renewable energy development in Indonesia is one of the governmentâ€™s programs to reduce carbon dioxide emission and dependence to fossil fuel. Bioethanol is an alternative energy that can be developed to replace solar fuel. Peat is a source of bio-ethanol which is very potential because of its abundant source in Indonesia. This research investigated the lifecycle of bio-ethanol from peat, resulting in carbon dioxide emission reduction and energy net. Fermentation method was used to produce bio-ethanol from peat. In the fermentation, yeast was used and the fermentation temperature was from 200C to 400C. The products were analyzed by a gas chromatograph (GC). The results showed that at the 10th day, the bioethanol production was the highest. This research also concerns to the side effects of by-products from bioethanol production. The use of by-products may improve the environmental performance and bioethanol energy until 30-70%. This research showed that bioethanol (from peat) development in Indonesia is much better compared to other countries.Â Â Â